Identification of Internal Academic Factors Affecting Academic Entrepreneurship: A Case Study - Prima Fithri; Rida Rahim; Donard Games; Alizar Hasan; Ikhwan Arief (Jurnal Optimasi Sistem Industri, 2021)
Academic Entrepreneurship is an entrepreneurial activity conducted by scientists/academics who market their research results commercially to achieve specific economic benefits or rewards. This research focuses on academic entrepreneurship that occurs at Andalas University. There is still a lack of academics whose research products for commercialization are about 22.73%. It is because there are factors that influence academic entrepreneurship activities at Andalas University. One of them is the internal academic factor. The internal factors are Control System, Organizational Culture, Human Resource Management System, Organizational Structure, and Academic Leadership Behavior. The purpose of this study is to analyze the university's internal factors on academic entrepreneurship. This research uses a quantitative approach derived from 106 Andalas University academics with Structural Equation Modelling (SEM) methods with SmartPLS Software. The result obtained in this study is that the control system exerts a positive and negative influence on academic entrepreneurship. In contrast, other factors have a significant positive influence on academic entrepreneurship. The research results show that the university's control system, organizational structure, and human resources had no significant positive effect on academics at Andalas University. Meanwhile, entrepreneurial behavior and organizational culture have a significant positive effect on academic entrepreneurship at Andalas University. Further research should be analyzed for all universities with innovative products and are ready for commercialization throughout Indonesia. This research is still a case study and needs to be developed.